Return of the mummy - Stine, R. L. (New York : Scholastic, 1994)
Returning to Egypt to help his uncle Ben and cousin Sari with an archaeological dig, Gabe learns about a curse that supposedly brings mummies back to life and thinks his uncle has become a victim.
"An Apple paperback."
4-6
560
560
Accelerated Reader AR
Keywords: Horror tales; Mummies -- Fiction; Egypt -- Antiquities -- Fiction